In-Vitro Antibacterial Properties of Ethanol and Methanol Extracts of Betel Leaves Collected from Different Areas of Bangladesh - Hossain, Md Sahadat; Das, Kamal Kanta; Acharjee, Mrityunjoy (Bangladesh Journal of Microbiology, 2019)
Current investigation depicted in-vitro antibacterial activity of available betel leaf (sweet, hot and fresh betel leaves) collected from different place of Bangladesh. The in-vitro antimicrobial activities of the ethanol and methanol extracts of the betel leaf were noticeable against tested bacteria. Among 3 categories of samples, the antibacterial action of ethanol extracts of hot betal leaf was found the highest against most of the bacteria except Klebsiella sp. and Staphylococcus sp., while the methanol extract showed antibacterial activity against all the pathogenic strains tested. The highest MIC (1mg/ml) and the lowest MIC values (25mg/ml) of hot betel leaf and sweet betel leaf were found against E. coli and all test organisms, respectively. This evidence revealed that betel leaf extracts can be used to combat against human pathogens. Bangladesh J Microbiol, Volume 34 Number 2 December 2017, pp 125-127